The relationship between digital finance and capital structure: A conceptual paper - Dianjie, Liang; Rahim, Ruzita Abdul (Edelweiss Applied Science and Technology, 2025)
The rapid development of digital finance has significant implications for corporate capital structure decisions. This conceptual paper explores the influence of digital finance on capital structure in the new digital environment, focusing on how digital finance innovations impact firms' financing decisions. Digital finance, including innovations like mobile banking and blockchain, has transformed the financial market. It has profoundly changed traditional financial institutions and enterprises by providing broader access to financial services at lower costs and easing financial constraints. Capital structure, the combination of debt and equity financing, significantly affects a firm's risk and financial performance. Traditional capital structure theories may need re-examination due to digital finance's impact. Through a synthesis of existing literature, the study reveals that digital finance enhances firms’ access to external financing, reduces financing costs, and strengthens governance through improved transparency and monitoring. These mechanisms enable firms to optimize capital structure, spur innovation, and improve ESG performance. The study further highlights digital finance in fostering entrepreneurial activity. Based on the findings, this paper proposes a theoretical framework to understand digital finance's role in capital structure, providing valuable insights for academics and practitioners in corporate finance, such as the role of digital finance in deleveraging campaigns.